KEBERADAAN DENDA ADMINISTRATIF TERKAIT PERATURAN GUBERNUR DKI JAKARTA NOMOR 33 TAHUN 2020 TENTANG PELAKSANAAN PSBB DALAM PENANGANAN COVID-19 DI PROVINSI DKI JAKARTA - Tomson Situmeang (Fakultas Hukum Universitas Kristen Indonesia, 2020)
Covid-19 is a dangerous virus. In Indonesia, many are infected and increasing every day. DKI Jakarta is the area most affected by Covid-19. The Governor of DKI Jakarta imposed Large-Scale Social Restrictions by issuing Governor’s Regulation No. 33 of 2020 which contains legal sanctions. An interesting thing was discussed about the existence of legal sanctions related to Governor’s Regulation No. 33 of 2020. The Provincial Government of DKI Jakarta has issued guidelines for the implementation of the PSBB. PSBB restricts activities, including: facilitating schools and workplaces; restrictions on religious activities; and/or restrictions on activities at public places or facilities. Governor’s Regulation No. 33 of 2020 is actually not necessary because the authority to regulate PSBB rests with the Central Government.